The Future of Africa: Challenges and Opportunities - Cilliers, Jakkie (Springer Nature, 2021)
This open access textbook offers a critical introduction to human and economic development prospects in Africa revolving around three questions: where is Africa today, what explains the current state, and, given historical trends and what we know about the world, where do we think the continent will be in 2040? And, a final question: what can we do to create a better tomorrow? It models ambitious progress in health, demographics, agriculture, education, industrialization, technological leapfrogging, increased trade, greater stability, better governance and external support. The book reviews the future of work/jobs, poverty and the impact of climate change. A combined Closing the Gap scenario presents a forecast of what could be possible by 2040. Each chapter suggests which policies might accelerate prospects for each sector. Written in an accessible style, and supported by a range of pedagogical features, this textbook introduces undergraduate and graduate students to the contemporary human and economic development prospects in Africa.